2021
DOI: 10.3748/wjg.v27.i48.8323
|View full text |Cite
|
Sign up to set email alerts
|

Dual therapy with zinc acetate and rifaximin prevents from ethanol-induced liver fibrosis by maintaining intestinal barrier integrity

Abstract: BACKGROUND Hepatic overload of gut-derived lipopolysaccharide dictates the progression of alcoholic liver disease (ALD) by inducing oxidative stress and activating Kupffer cells and hepatic stellate cells through toll-like receptor 4 signaling. Therefore, targeting the maintenance of intestinal barrier integrity has attracted attention for the treatment of ALD. Zinc acetate and rifaximin, which is a nonabsorbable antibiotic, had been clinically used for patients with cirrhosis, particularly those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…analyzed miRNA expression in alcoholics to further characterize the genetic influence of alcoholism and the influence of alcohol consumption on predicted target mRNA expression, which involved THBS2 ( 49 ). In mice treated with ethanol and CCl 4 , down-regulation of TIMP1 effectively inhibited hepatic fibrosis and activation of hepatic stellate cell ( 50 ). Clinical studies have found that alcohol consumption in adolescents leads to elevated serum TIMP1 concentrations ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…analyzed miRNA expression in alcoholics to further characterize the genetic influence of alcoholism and the influence of alcohol consumption on predicted target mRNA expression, which involved THBS2 ( 49 ). In mice treated with ethanol and CCl 4 , down-regulation of TIMP1 effectively inhibited hepatic fibrosis and activation of hepatic stellate cell ( 50 ). Clinical studies have found that alcohol consumption in adolescents leads to elevated serum TIMP1 concentrations ( 51 ).…”
Section: Discussionmentioning
confidence: 99%
“…[37], insulin secretion [38], and adipokine secretion, etc. Indeed, as the important metabolites of anaerobic bacteria in gut, the acetate was also implied as a key regulator of intestinal homeostasis [39], intestinal barrier integrity [40], intestinal inflammation [41], etc. All these impacts could profoundly affect the body's metabolism and thus influence the function of brown adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…For example, successful results have been achieved with the use of hepatotoxins or viral proteins such as CCl 4 , a high-fat diet, acetaminophen, iron, or diethylnitrosamine (DEN). 51 In Fujimoto et al’s 51 study, female C57BL/6J mice were fed with an LDE diet with 2.5% (v/v) of total calories being ethanol for 8 weeks. One mL/kg of CCl 4 administered intraperitoneally twice a week.…”
Section: Current In Vivo Experimental Models Used In Alcohol Toxicitymentioning
confidence: 99%